2011
DOI: 10.1259/bjr/95862259
|View full text |Cite
|
Sign up to set email alerts
|

Digital tomosynthesis—a new lease of life for the intravenous urogram?

Abstract: Objectives: Digital tomosynthesis is a new digital technique based on conventional Xray tomography. It acquires multiple low-dose projections during a single sweep of the X-ray tube, which are reassembled to provide high-resolution slices at different depths. Suggested uses include visualisation of pulmonary nodules, mammography, angiography, dental imaging and delineation of fractures. This study aims to evaluate its potential role as part of an intravenous urogram (IVU) by assessing the diagnostic quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, it administers a high dose of radiation to patients and follow-up is expensive, thus limiting its application. Previous studies determined that the conventional and low effective doses of UMDCT are higher than those of DTS (4,(8)(9)(10). In the present study it was determined that the detection rate of DTS prior to bowel preparation was 94.2%.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, it administers a high dose of radiation to patients and follow-up is expensive, thus limiting its application. Previous studies determined that the conventional and low effective doses of UMDCT are higher than those of DTS (4,(8)(9)(10). In the present study it was determined that the detection rate of DTS prior to bowel preparation was 94.2%.…”
Section: Discussionmentioning
confidence: 60%
“…The Kidneys-Ureters-Bladder (KUB) radiograph is able to effectively identify the location of calculi (3). However, due to the influence of intestinal gas and the overlapping area of the abdominal cavity, KUB radiography has certain disadvantages, including low-density resolution, low sensitivity and low accuracy (4). Unenhanced multidetector computed tomography (UMDCT) is the procedure of choice for the radiological evaluation of patients with renal colic (5).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity was 64 and 76% for stones between 2 and 5 mm and those larger than 5 mm, respectively. The radiation dose of digital tomosynthesis was only slightly increased in comparison to digital radiography and was substantially lower than CT or even low-dose CT. A second study by Wells et al compared the diagnostic quality of IVP with digital tomosynthesis to conventional IVP [57]. The addition of digital tomosynthesis to conventional IVP increased the diagnostic quality from 46.5 to 95.5% with a mean radiation dose reduction of 56%.…”
Section: Digital Tomosynthesismentioning
confidence: 99%
“…9 Wells et al studied the diagnostic quality of an IVU performed with the technique of DT. 10 In their study, two uro-radiologists compared a traditional IVU with an IVU performed with DT. They found that 95.5% of the IVU with DT were of subjective diagnostic quality v 46.5% of the traditional IVUs.…”
Section: Introductionmentioning
confidence: 99%